Characterization and antimicrobial properties of fluorine-rich carbon films deposited on poly(lactic acid) - D. Boonyawan (2018)
This study describes the effect of fluorine contents on the properties of carbon films deposited on poly(lactic acid) (PLA) substrate using plasma enhanced chemical vapor deposition (PECVD) technique. A mixture of acetylene (C2H2) and carbon tetrafluoride (CF4) gas was utilized for film deposition. The thickness of the deposited carbon film was in the range of 150-350nm. The film's deposition rate was found to increase with the decreasing CF4concentration in the gas mixture. Fourier transform spectroscopy revealed the presence of C-F bonds, and X-ray photoelectron spectroscopy showed that the C-C bonds of the carbon film were replaced by the C-CFxbonds. This affirms that the films have a polymer-like structure. High concentration of fluorine (up to 25at.%) could be obtained when 50% of CF4was used. PLA coated with F-rich carbon film showed hydrophobic character due to the formation of -CFxbonds. The film with a high concentration of fluorine showed excellent performance on reduction of Escherichia coli (E. coli) growth. © 2011 Elsevier B.V.